The Reproduction of Meretrix meretrix Clams in The Kambu River Estuary, Southeast Sulawesi: Reproduksi Kerang Tahu (Meretrix meretrix) di Muara Sungai Kambu, Sulawesi Tenggara - Bahtiar; Muhammad Fajar Purnama; Rahmadhani; Muhammad Nur Findra (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2022)
Meretrix meretrix is a degraded resource in Kendari Bay waters, but its reproductive pattern is not fully known.. This study aims to determine the level of gonad maturity, gonadal maturity index, fecundity and the size of the first gonad maturity of M. meretrix at the Kambu River estuary, Kendari Bay, Southeast Sulawesi. This research was carried out at the Kambu River estuary for 6 months from August 2021-January 2022. These clams were taken randomly representing all size classes as many as 300 birds during the study. M. meretrix were observed for gonad color and gonad development microscopically, then the length and weight of the gonads were measured using a caliper and analytical balance with an accuracy of 0.5 mm and 0.0001g, respectively. The results showed that the development of male and female gonads was relatively simultaneous, which was dominated by mature gonads (III-IV) in each month of observation. TKG I-V was found in every month of observation. The gonad maturity index of males and females were 4.92-6.00 and 5.53-6.32, respectively. The fecundity of M. meretrix ranged from 4882-85677 grains. The first mature size of the gonads of male and female M. meretrix is 20 mm.